Asylum seekers' access to the Icelandic labor market - Tryggvardóttir, Helga Katrín (School of Social Sciences, 2023)
The aim of this paper is to analyse the access of asylum seekers to Icelandic labour market while their asylum application is in process. The analysis is framed in the context of asylum seekers’ precarious position, both on the labour market and in terms of their legal status. Asylum seekers’ access to the labour market is limited to a temporary working permit that not all asylum seekers can apply for. Those who could apply for a work permit were faced with other barriers to participation on the labour market. Despite most of the participants in the research wanting to work in Iceland their access to the labour market was limited. A few of the participants tried to apply for a working permit and went to great lengths to find a job and keep it. The greatest barriers to finding and keeping a job was their status as asylum seekers, the lengthy work permit application process and the wait for a social security number. The paper is based on participatory research and interviews with asylum seekers. The main findings are that asylum seekers’ access to Icelandic labour market is very limited and can lead to their social exclusion. These limits risk putting asylum seekers in a precarious position towards employers and the state. Markmið þessarar greinar er greina frá niðurstöðum könnunar um aðgengi hælisleitenda að íslenskum vinnumarkaði á meðan þeir eru í hælisumsóknarferli. Kannað var hversu vel hælisleitendum gekk að komast inn á íslenskan vinnumarkað og hvort samræmi væri á milli lagalegrar heimildar þeirra til að sækja um atvinnuleyfi og raunverulegs aðgengis að vinnumarkaðnum. Greinin byggist á vettvangsathugunum og viðtölum við hælisleitendur. Þrátt fyrir að flestir viðmælendur hafi viljað geta unnið fyrir sér reyndist aðgengi þeirra að vinnumarkaðnum takmarkað. Nokkrir viðmælendanna reyndu að sækja um atvinnuleyfi og lögðu mikið á sig til að finna vinnu og halda henni. Helstu hindranirnar í vegi fyrir þátttöku á vinnumarkaðnum var lagaleg staða þeirra, langdregið umsóknarferli og bið eftir kennitölu. Helstu ...